INCREASED ANTI-INFLUENZA EFFICACY OF OSELTAMIVIR (TAMIFLU®) AND UMIFENOVIR (ARBIDOL®) BY COMBINED USE WITH KAGOCEL® - A. F. Popov; A. I. Simakova; K. A. Dmitrenko; M. Yu. Shchelkanov (Антибиотики и Химиотерапия, 2020)
An open prospective comparative study of the efficacy of influenza monotherapy with antiviral drug versus combination therapy of two antiviral drugs with different mechanisms of action (within the limits of registered medical use for the drug) was performed in 200 patients with influenza A (H1N1) pdm09. In all patients, the clinical diagnosis was confirmed by the indication of the virus in nasopharyngeal washings by polymerase chain reaction with pre-reverse transcription (RT-PCR) in real time. All patients were randomly divided into 4 groups of 50 people, they were equivalent in terms of admission to hospital, age, sex, and the length of treatment from the onset of the disease. Group 1 received monotherapy with Umifenovir 800 mg/day in 4 divided doses for 5 days; Group 2 - monotherapy with Oseltamivir 150 mg/day in two doses for 5 days; Group 3 - Umifenovir according to the described scheme in combination with Kagocel 72 mg/day in 3 doses for the first 2 days and 36 mg/day in 3 doses in the following 2 days; Group 4 - Oseltamivir according to the described scheme in combination with Kagocel 72 mg/day in 3 doses for the first 2 days and 36 mg/day in 3 doses in the following 2 days. Criteria for the clinical efficacy of antiviral therapy were the time of temperature normalization, decrease of intoxication, catarrhal symptoms, frequency of the main clinical manifestations, and the frequency of complications development after the end of treatment in comparison with the state before it began. In assessing the duration of the symptomatology, the end point was the absence of symptoms of the disease within 24 hours. The study showed that the combination of etiotropic drugs Oseltamivir (Tamiflu®) and Umifenovir (Arbidol®) with the antiviral agent Kagocel® makes it possible to significantly improve the therapeutic efficacy compared with the corresponding monotherapy, which is expressed by a decrease in the frequency of manifestation of the main clinical indicators, a reduction in the duration of clinical symptoms, and a decrease in the frequency of complications. Good tolerability of treatment by patients was noted.